Self-Efficacy: In-Depth Study of PAI Students' Teaching Readiness Through Teaching Practices 1 (Microteaching) - Siti Sarifah; Hamdanah Hamdanah; Surawan Surawan (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Self-efficacy is an individual's belief in his or her ability to achieve the desired results in a particular context, in this case the readiness to teach through microteaching-1, which is mostly aimed at prospective teacher students, especially in this research, students of the Faculty of Islamic Religious Education study program Tarbiyah and Teacher Training, Palangka Raya State Islamic Institute. The research method used is descriptive qualitative research. Data collection techniques include interviews with PAI FTIK IAIN Palangka Raya students who have carried out PM 1, direct observation and documentation analysis. Data analysis involves the process of data collection, data reduction, data presentation and conclusions. The findings from the research show that the self-efficacy of PAI FTIK IAIN Palangka Raya students is at a fairly good level, where they have high confidence in their teaching abilities. Students' teaching readiness is also at a good level, indicated by thorough preparation in implementing Teaching Practices-1 in creating teaching modules and the learning media used. There is a significant positive impact between self-efficacy and teaching readiness. Students with a high level of self-efficacy demonstrate better teaching readiness and are able to master teaching skills.